2009
DOI: 10.1111/j.1468-3083.2009.03087.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between the PD1.3A/G polymorphism of the PDCD1 gene and systemic lupus erythematosus in European populations: a meta‐analysis

Abstract: This meta-analysis demonstrates a significant association between PD1.3A and SLE among non-Spanish European descents, while a negative association was observed in Spanish population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Prokunina et al (2002) found that a regulatory single-nucleotide polymorphism (SNP) PD1.3G/A located in the programmed cell death 1 (PDCD1) gene is involved in susceptibility to SLE in Swedish, European American, and Mexican cases. Metaanalysis has demonstrated a significant association between PD1.3A and SLE among non-Spanish European descendants, while a negative association was observed in a Spanish population (Liu et al, 2009). In this study, we investigated the associations between rs2227981, rs2227982, and rs11568821 polymorphisms of the PDCD1 gene and SLE, but did not find any.…”
Section: Discussionmentioning
confidence: 86%
“…Prokunina et al (2002) found that a regulatory single-nucleotide polymorphism (SNP) PD1.3G/A located in the programmed cell death 1 (PDCD1) gene is involved in susceptibility to SLE in Swedish, European American, and Mexican cases. Metaanalysis has demonstrated a significant association between PD1.3A and SLE among non-Spanish European descendants, while a negative association was observed in a Spanish population (Liu et al, 2009). In this study, we investigated the associations between rs2227981, rs2227982, and rs11568821 polymorphisms of the PDCD1 gene and SLE, but did not find any.…”
Section: Discussionmentioning
confidence: 86%
“…However, PD-1.3 gene was found to be polymorphic in Iran, while A allele frequency was 9% and 11% in patients and controls, respectively. Earlier studies in the European population also showed polymorphism in this region [28], while in the Eastern Asian populations, this region was revealed to be non-polymorphic [19,29]. Such differences could be explained considering different ethnicities in the different regions of the world.…”
Section: Discussionmentioning
confidence: 77%
“…Two previous meta-analyses [33, 34] were conducted almost at the same time(in 2009) to explore the association between PDCD1 polymorphisms and SLE. Liu et al [33]paid attention to the effect of PD1.3 polymorphism on SLE risk in European populations by combining results in meta-analysis.…”
Section: Discussionmentioning
confidence: 99%